1. ## Factorisation Help

Hi I need help with these equations
V (squared)-36

9K (squared)-4

2C(squared)+4=1

1-9K(squared)=0

thanks

2. Originally Posted by mat
Hi I need help with these equations
V (squared)-36

9K (squared)-4

2C(squared)+4=1

1-9K(squared)=0

thanks
all of them involve the factoring pattern of $\displaystyle a^2-b^2=(a+b)(a-b)$

3. thanks for the reply so
V (squared)-36 = (v+6) (v-6)

9K (squared)-4 = no simplify

but isn't
2C(squared)+4=1
2c(squared)=1-4
c(squared)=-3
c squared=-3/2
c=Square root of -1.5

1-9K(squared)=0
9k squared=-1
k squared=-1/9
k=square root of -0.1111

how do I write square in this forum?

4. Originally Posted by mat
V (squared)-36 = (v+6) (v-6)

9K (squared)-4 = no simplify

but isn't
2C(squared)+4=1
2c(squared)=1-4
c(squared)=-3
c squared=-3/2
c=Square root of -1.5

1-9K(squared)=0
9k squared=-1
k squared=-1/9
k=square root of -0.1111

how do I write square in this forum?
all of those do factor $\displaystyle 9k^2-4\Rightarrow{(3k)^2-2^2}\Rightarrow{(3k+2)(3k-2)}$ same with the $\displaystyle 1-9k^2\Rightarrow{1^2-(3k)^2}\Rightarrow{(1-3k)(1+3k)}$

5. O...and if you ever get the squareroot of a negative number you probably did it wrong because you see $\displaystyle \sqrt{-a},\forall{a}>0=\sqrt{a}i$ where $\displaystyle i\equiv{\sqrt{-1}}$...sound familiar? if not then what I said is right...they wouldnt throw these at you without teaching you...so if you get the squareroot of a negative number you probably did the question wrong

6. 1. v(squared) - 36=v(squared) - 6(squared)=(v-6)(v+6)
2. 9k(squared) - 4=(3k +6)(3k-6)
3. 2c(squared)+4=1
or 2c(squared) =-3
or 4c squared=-3
or c squared=-3/4 i.e. -o.75
or c= square root of -0.75
4. 1-9k(squared) =0
or 1(squared) - 9k(squared)=0
or (1 + 9k)(1-9k) =0
so 1+9k=0 i.e. 9k=-1 i.e. k =-1/9 i.e. -0.111111111111...

7. Originally Posted by sabyasachi
or 2c(squared) =-3
or 4c squared=-3
or c squared=-3/4 i.e. -o.75
or c= square root of -0.75
isn't the answer sqaure root of-1.5

just a couple more questions
I have the quadratic formula x=-b+-sqaure root of B squared minus 4ac
divided by 2A
hope you understand this
how do i do these calculations
x squared-3x-8=0

3H squared-10=0

2C squared+4=1

3K squared +2k-5=0